1974
DOI: 10.2105/ajph.64.7.717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of legalized abortion on neonatal mortality and obstetrical morbidity at Harlem Hospital Center.

Abstract: A significant cost differential obviously exists between inpatient and outpatient abortion services. The feasibility of providing outpatient vacuum aspiration procedures has been adequately demonstrated during the past few years, and as the fraction of women seeking early abortion increases the use of outpatient facilities should also increase. The effects of such a shift were also investigated.As the fraction of outpatient abortions was increased from a low of 10 per cent to a high of 90 per cent, the costs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Initial research generally supported the link between increased use of abortion and improved birth outcomes (Lanan, Kohl, and Bedell 1974;Glass et al 1974;QuIck 1978). However, not untIl Grossman and Jacobowitz (1981) and Corsan and Grossman (1985) was the impact of abortion services quantified in a multivariate context.…”
Section: Joyce Departirnt Of Economics Lona College New Pochelle Ny mentioning
confidence: 99%
“…Initial research generally supported the link between increased use of abortion and improved birth outcomes (Lanan, Kohl, and Bedell 1974;Glass et al 1974;QuIck 1978). However, not untIl Grossman and Jacobowitz (1981) and Corsan and Grossman (1985) was the impact of abortion services quantified in a multivariate context.…”
Section: Joyce Departirnt Of Economics Lona College New Pochelle Ny mentioning
confidence: 99%
“…Previous studies of the legalization of abortion suggest that these reporting effects may be important. For example, Glass et al (1974) and Lanman et al (1974) found that increases in the number of legal abortions following legalization reflected decreases in the number of illegal abortions, rather than any increase in the pregnancy rate.…”
Section: B) Probability Of a Birthmentioning
confidence: 99%
“…Hence, poor women in states that do not pay for abortions under Medicaid may be unable to afford them. 1 There is a large body of literature documenting the relationship between the distribution of birth outcomes and the availability of abortion services (Glass et al, 1974;Lanman, Kohl and Bedell, 1974;Quick, 1978;Grossman and Jacobowitz, 1981;Corman and Grossman, 1985;Joyce, 1987;Grossman and Joyce, 1990;. These studies all suggest that the women who are most likely to have unhealthy babies if abortion is not available, are also most likely to choose abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Sweden has had a declining low birth weight rate and low perinatal mortality figures for many years, but the part played by legal abortion in this trend is uncertain [16,17]. Studies from New York [6,12] have claimed a reduction in neonatal mortality rates following introduction of liberalized abortion. This decrease wasattributed to the smaller numbers of very low birth weight (500 to 1000 grams) babies being born.…”
Section: Perinatal and Neonatal Mortalitymentioning
confidence: 99%